Clinical outcome in patients treated with simultaneous integrated boost – intensity modulated radiation therapy (SIB-IMRT) with and without concurrent chemotherapy for squamous cell carcinoma of the anal canal. (2nd June 2016) - Tomasoa, Nathalie B.; Meulendijks, Didier; Nijkamp, Jasper; Cats, Annemieke; Dewit, Luc
Abstract: Background and purpose To retrospectively evaluate locoregional control (LRC), survival and toxicity in anal cancer patients treated with simultaneous integrated boost – intensity modulated radiation therapy (SIB-IMRT) ± concurrent chemotherapy. Methods and materials Patients with squamous cell anal carcinoma stage T1(≥1 cm)–4, N0–3, M0–1 were included. All patients were treated with SIB-IMRT to a total dose of 59.4 Gy delivered to the primary tumor and macroscopically involved lymph nodes and 49.5 Gy to elective lymph node areas. If macroscopic residual tumor was still present in the fifth week of irradiation, a sequential boost of 5.4 Gy was given. Concurrent chemotherapy was administered in locally advanced cases. Acute and late toxicity were scored. Results One hundred and six patients treated consecutively between April 2006 and December 2012 were included. Eighty-seven (82.1%) patients received concurrent chemotherapy. The median follow-up was 47 months (range 2–104 months). Ninety-eight patients reached a clinical complete response (92.5%). Four-year actuarial LRC rate, overall survival and colostomy-free survival were 79%, 77% and 77%, respectively. Acute grade ≥3 toxicity occurred in 67.9% of the patients. Late grade 3 toxicity was seen in 16 patients (15.1%). Conclusions SIB-IMRT ± concurrent chemotherapy for anal cancer was effective with acceptable toxicity.